Application of conducting atomic force microscopy to the study of Ni-YSZ SOFC electrode materials (Canadian Institute of Mining, Metallurgy and Petroleum, 2005)
Commercial SOFC systems will likely utilize hydrocarbons or hydrogen produced from hydrocarbon fuels and therefore will likely be exposed to sulfur impurities. Conducting-Atomic Force Microscopy (C-AFM) is a scanning probe microscopy technique which maps both sample topography and conductivity with tens of nanometers resolution. In Ni-YSZ, C-AFM measures the resistance of the metallic network at scanned locations, with the ability to differentiate between interconnected and isolated metallic particles. We have applied C-AFM to Ni-YSZ SOFC anode materials, with the goal of monitoring changes in the conductivity of the Ni anode network resulting from SOFC degradation processes, such as H2S poisoning.